Penerapan Relaxing Prenatal Yoga Terhadap Tingkat Kecemasan Ibu Hamil Trimester III Dengan Pendekatan Kualitatif - Titi Purwitasari Handayani; Rita Ayu Yolandia (WOMB Midwifery Journal, 2025)
Pregnancy and childbirth are natural processes and changes occur physically and psychologically that women need to adapt. Psychological changes that occur during pregnancy, one of which is anxiety that occurs in the third trimester. Anxiety in pregnancy is associated with increased obstetric complications. One of the obstetric cares performed to reduce anxiety in the labor with relaxation, prenatal yoga. The purpose of this study was determine the effect of the application of relaxing prenatal yoga on the level anxiety of pregnancy women in the thirdh trimester. This research uses qualitative methods with a case study approach. The results of the study of respondents who were given a relaxing prenatal yoga intervention experienced a decrease in anxiety scores. Meanwhile, respondents who were not given the intervention experienced a decrease in anxiety scores but at each meeting different anxiety scores. From the results of the study, it can be concluded that relaxing prenatal yoga can help control the anxiety of pregnant women in the third trimester if routinely done. This study can provide a means of information or additional knowledge about the effect of relaxing prenatal yoga to the anxiety level of pregnant women in the third trimester.